A comparative study on the clinical effect of the treatment of pathological scars in young and middle-aged women with the combination of Chinese and western medicine. Issue 25 (19th June 2020) - Liu, Ya-hong; Xiang, Jun; Han, Pei-pei; Yang, Chun; Wang, Yu-zhen; Wang, Wei; Zhang, Ping-an
Abstract: Introduction: Pathological scar is the abnormal manifestation of skin fiber hyperplasia caused by the failure of normal healing after skin damage. At present, there are many clinical treatments for pathological scars. However, there is no cure for clinically effective pathological scars with high recurrence rate. In this study, we will use a combination of Chinese and western medicine treatment methods to evaluate the clinical efficacy and related indicators of young and middle-aged female patients who meet pathological scars, looking for an objective and effective treatment method for pathological scars. Methods/design: In this study, we will use our own front-to-back clinical research method. We plan to include 120 young and middle-aged female patients who meet the diagnostic criteria for pathological scars. The untreated pathological scars of the enrolled patients will be used as blank controls. The intervention group will be given conventional western medicine treatment and combined Chinese and western medicine treatment. The assessment of scar area, color, hardness, thickness, itching, and pain was recorded for 8 weeks of treatment. Discussion: This trial may provide evidence regarding the clinical effectiveness, safety, and cost-effectiveness of traditional Chinese medicine for patients with pathological scars. Trial registration: ClinicalTrials.gov, ChiCTR2000032187, Registered on April 22, 2020.